Child-safe organisations : a wise investment? - Budiselik, William Robert (Curtin University, 2010)
This thesis explores how in the last two decades a ‘child-safe organisations movement’ has emerged in Australia. The thesis title does not signal that the question posed therein is answered in this project, or even that it is answerable. The title is an invitation to the reader to hold the question in their mind as they read the thesis.This thesis addresses two research questions: What is a child-safe organisation? How can an organisation’s child-safe status be effectively represented to stakeholders? The outcomes of this project include a child-safe organisations framework and its critique. These are offered to those involved in organisations providing services to children as stimuli for reflection and loose scripts for enactment.The child-safe organisations framework and its critique were developed within interpretivist theoretical traditions and assumptions. Qualitative research methods consistent with these traditions were utilised to derive data from various sources including organisations’ stakeholders and purposively selected professionals (social workers, lawyers, administrators and insurers) to develop the framework.The research questions’ context is established by identifying the emergence of an Australian child-safe organisations movement. Impetus for the movement’s emergence came from revelations in the mid-1980s about child abuse in children’s institutions and then from recommendations of the Royal Commission into the New South Wales Police Service, which made findings about paedophilia. The thesis argues the movement’s advice can be typologised as good management, child protection, children’s rights and injury reduction.The thesis’ relevance and topicality has become more evident throughout the period of the project. In 2009 the Council of Australian Governments announced a specific strategy within a broad national framework to develop a nationally consistent approach to working with children checks and child safe organisations across jurisdictions (Protecting children is everyone's business: National framework for protecting Australia's children 2009-2020, 2009).